AutoCAD 2000 : the complete reference - Cohn, David S. (Berkeley, CA : Osborne, 2000)
This book provides knowledges to locate instructions for using specific AutoCAD commands, use the table of contents or the index; to help you better understand its organization.
Keywords: AutoCAD; Computer graphics; Computer graphics; AutoCAD